Continuous media e-mail on the Internet infrastructure inadequacies and a sender-side solution. - Turner, D.A.
This article examines how the Internet's e-mail infrastructure should evolve to better support continuous media e-mail, such as audio and video. We assert that the problem is not simply a matter of adding the obvious new functionality to user agents (mail readers), such as audio and video capture, but requires the adoption a new delivery model. We do this by examining the problems that arise using current methods to deliver video messages, and we show how sender-side storage and media streaming solve these problems. Finally, we describe an implementation strategy that requires changes only to individual sender systems, but enables CM e-mail to be delivered universally to any recipient, thus providing a realistic evolutionary path that can be adopted incrementally by individual mail systems
Keywords: Internet; Audio capture; Continuous media e-mail.; Delivery model; E-mail infrastructure; Mail readers; Media streaming; Privacy; Security; Sender-side solution; Sender-side storage; User agents; Video capture; Video message delivery